2021
DOI: 10.3389/fpsyg.2021.643120
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Networks of Interlanguage Across L2 Modalities and Proficiency Levels

Abstract: Over time, interlanguage studies have shifted from early qualitative to quantitative studies of specific linguistic structures. However, the focus of these studies is usually on one aspect of an interlanguage instead of the whole system. The ideal object of interlanguage research is a second language (L2) learner language system, for only in this way can the entire L2 learning process can be examined. As a self-organizing and self-regulated system, the panorama of interlanguage can be revealed objectively thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…For example, Jiang et al (2019) applied a syntactic network approach and discovered that English L2 learning is characterized by a gradual approximation to the target language, rather than a sudden emergence as in L1 development. In another study, Hao et al (2021) found varying regularities in the development of a syntactic network between interlanguage and native language acquisition, highlighting the network parameters' ability to differentiate interlanguage modalities and indicate L2 pro ciency.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Jiang et al (2019) applied a syntactic network approach and discovered that English L2 learning is characterized by a gradual approximation to the target language, rather than a sudden emergence as in L1 development. In another study, Hao et al (2021) found varying regularities in the development of a syntactic network between interlanguage and native language acquisition, highlighting the network parameters' ability to differentiate interlanguage modalities and indicate L2 pro ciency.…”
Section: Introductionmentioning
confidence: 91%
“…The network parameters that we are most interested in are those closely related to language pro ciencies (see Jiang et al, 2019;Hao et al, 2021;Chen, 2021), including clustering coe cient (C), average path length (< l>), and clusters (cl), etc. For comparison, we also investigated some common network parameters, such as network size (n), number of edges (m), network density (ND), and network centrality (NC).…”
Section: Network Parametersmentioning
confidence: 99%
“…Prior studies demonstrate the feasibility of using the complex network approach to characterize and classify human languages, including the exploration of statistical patterns of different languages, stylistic research (Ferrer-i-Cancho et al, 2004;Liu, 2008a), typological properties of languages (Liu and Xu, 2011), hierarchical structures of a language (Chen et al, 2015), the evolution of languages (Cui et al, 2017;Chen et al, 2018), and linguistic features in language learning (Jin and Liu, 2016;Jiang et al, 2019;Hao et al, 2021). It is probable that network properties can also discriminate linguistic features of different interpreting types.…”
Section: Introductionmentioning
confidence: 99%